Ricardian Equivalence and Non Equivalence: An Overview - Stefano Toso (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 1989)
This paper surveys some of recent theoretical developments in the Ricardian equivalence debate.
Keywords: 330